Zirconium modified pomegranate peel for efficient removal of arsenite from water - Poudel, Bhoj Raj; Ale, Dhan Shree; Aryal, Ram Lochan; Ghimire, Kedar Nath; Gautam, Surendra Kumar; Paudyal, Hari; Pokhrel, Megh Raj (BIBECHANA, 2022)
We developed a novel biosorbent based on zirconium-modified pomegranate peel (SPP@Zr) for efficient arsenic (As(III)) removal from water. SEM, EDX, XRD, and FTIR were used to characterize the prepared biosorbent. The batch adsorption method was used to evaluate the adsorption viability of biosorbents for the removal of As(III) from water. The EDX analysis of saponified pomegranate peels (SPP) before and after Zr (IV) loading demonstrated that ion exchange was the preferred metal loading technique. As (III) adsorption is very pH-dependent, with the maximum adsorption occurring at pH 8.0. The maximum As(III) adsorption capacity of SPP@Zr was found to be 82.0 mg/g. According to isotherm and kinetic modeling studies, the experimental results fitted well with the Langmuir isotherm and pseudo-second-order kinetic modeling. The spent biosorbent may be easily regenerated and reused using an alkaline solution. Hence, SPP@Zr is proving to be a promising biosorbent for uptake of As (III) from water. BIBECHANA 19 (2022)1-13